BrGSTF12, an anthocyanin-related glutathione S-transferase gene, is essential for light-induced anthocyanin accumulation in zicaitai (Brassica Rapa Var. purpuraria) - Mei Fu; Guihua Li; Mengting Lu; Shizheng Jiang; Umer Karamat; Imran Khan; Juxian Guo (BMC Plant Biology)
Abstract Background Anthocyanins are a group of polyphenolic pigments that play essential biological roles and significantly influence the quality of agricultural produce. Bioinformatics approaches were employed to predict and identify potential genes involved in the sequestration of anthocyanins in Zicaitai (Brassica rapa var. purpuraria) utilizing data from the transcriptome database. Results In this study 0-hour light (dark) and 8-hour light treatments of Zicaitai were examined using transcriptome analysis. RNA-seq analysis indicates that 24 important anthocyanin biosynthesis genes, including 5 PAL, 3 4CL, 3 CHS, 3 CHI, 2 F3H, 1 DFR, 2 ANS, and 5 UGFT were significantly differentially expressed between 0-hour and 8-hour light treatment. The transcript levels of the glutathione S-transferase gene, BrGSTF12, were significantly higher at 8 h compared to 0 h. BrGSTF12 expression level correlated with the patterns of anthocyanins content in each tissue of Zicaitai. Functional complementation in the Arabidopsis tt19 mutant further demonstrated that BrGSTF12 was involved in the transport of anthocyanins. Additionally, expression analysis showed that BrMYB114 levels were significantly elevated at 8 h, and dual-luciferase assays confirmed that BrMYB114 effectively trans-activated the promoter of the BrGSTF12 gene. Conclusion This study provides molecular evidence supporting the regulatory roles of BrGSTF12 and BrMYB114 in enhancing anthocyanin accumulation in Zicaitai under light induction. The findings contribute to a deeper understanding of the mechanisms behind anthocyanin biosynthesis and transport, offering valuable insights that could aid in breeding anthocyanin-rich crops, and paving the way for new opportunities in crop development.